The Problem of Interpreting the Defense of Compulsory (Noodweer and the Defense of Compulsory Exceeding the Limits (Noodweer Excess) in the Indonesian Criminal Legal System - Nur Saleha; Kiki Kristanto; Hilyatul Asfia (Green Publisher Indonesia, 2026)
The legislation contains several articles that seem ambiguous and even unclear in their intent, requiring further interpretation. This study aims to analyze noodweer and noodweer excess in the Indonesian criminal law system and the limits in the use of noodweer and noodweer excess in the Indonesian criminal system. This research is a type of normative juridical research, with data sourced from primary and secondary sources. Data were collected through literature studies and analyzed using deductive methods. The results of this study describe the emergence of a sense of injustice in society; legal certainty becomes unclear and disrupts the realization of legal objectives, and the risk of human rights violations arises. This is caused by the deep disparity in the imposition of sanctions on similar cases, both in the charges and the positioning of the case. As for the limitations in the use of noodweer and noodweer excess in the Indonesian criminal system, it is the formulation of a single limitation in understanding what the limits of noodweer and noodweer excess are, departing from the elements in Article 49 paragraph (1) and paragraph (2) of the Colonial Criminal Code and Articles 34 and 43 of the National Criminal Code. These criteria can be achieved through the revision of legislation or the preparation of Sentencing Guidelines or Sema (Supreme Court Circular Letter).